Smart monitoring system of Najran dam - A. H. M. Almawgani; M. A. Alshorman; M. A. Alyami; H. M. Alhmammi; D. S. Almahri; M. A. Alkhuraym; A. H. Alwasel (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Najran city faces the flood situation every year due to intensive rain and climatic disturbances. Flooding also causes loss of money, along with loss of life and property and the destruction of agriculture and livestock. Thus, this project proposes a conceptual framework with three main phases: monitoring the water level inside the dam and level in water stream before and after the dam, controlling the opening and closing of the dam gate and measuring the water pressure at the dam barrier. In the case of high water level dam is monitored through water sensors placed at the top of the dam and then these sensors give a reference to the stepper motor and the flow of the stepper motor is controlled by the dam gate. The experimental results shows that the proposed system has the capability to reliably tackle the flood water. It can accurately measure the water level and control the gate of dam as soon as the level of the water reaches to danger level and water pressure at the barrier is measured by the sensor. The developed real-time monitoring system in Najran dam will help authorities to take preventive actions to deal with flood disaster.